PENERAPAN MODEL PEMBELAJARAN THINK PAIR AND SHARE (TPS) PADA PEMBELAJARAN IPS SISWA KELAS V SD NEGERI 71 LUBUKLINGGAU - Tri Nana Sari; Andriana Sofiarini; Armi Yuneti (STKIP Bina Bangsa Meulaboh, 2022)
AbstractThis study aims to determine the social studies learning outcomes of fourth grade Students of SD Negeri 71 Lubuklinggau after the Think Pair and Share (TPS) Learning Model has been significanily completed. This research method uses experimental research methods with pre-test and post-test experimental designs. Sampling was taken from the total population considering that there is only one class population, so the population is the sample in the study, the sample used is saturated sampling while the sample in the study is class V students, totaling 24 Sludents. The instrument used by the researcher was in the form of essay guestions, which amounted to 8 guestions. Data collection was taken by using a test technigue. The data were analyzed using the